Deconstruction of Male and Female Characters’ Qualities in Zootopia - William Teddy (Institute of Research and Community Outreach - Petra Christian University, 2019)
This research aims to analyze the representation of male and female characters’ qualities that are portrayed in Zootopia. The research also aims to show how the qualities are deconstructed as well as how to deconstruct the deconstruction in the movie as a method of analysis. Through the analysis the writer finds that the representation of qualities in Zootopia follows the traditional gender stereotypes, where men are considered superior than women. However, as the story progresses, the writer finds that the qualities in the movie are gradually deconstructed, showing that women are superior than men. After deconstructing the deconstruction in the movie, the writer finds that meaning can “disseminate” or can be perceived in different ways. Furthermore, from the analysis, the writer finds that both oppositions are actually interdependent to each other and complement as a whole. This means neither of the oppositions is stronger or weaker than the other. Keywords: Gender roles, Masculine and Feminine Gender Stereotypes, Deconstruction, Binary Opposition, Violent Hierarchy